Preparation and characterization of mucoadhesive microcapsules of salbutamol sulfate - Patil, Pradnya; Rao, N G Raghavendra; Hiremath, Doddayya (Asian Journal of Pharmaceutics (AJP), 2014)
Salbutamol sulfate microcapsules with a coat consisting of sodium alginate and mucoadhesive polymer such as sodium carboxy methyl cellulose (NaCMC), methyl cellulose (MC), carbopol-934, and hydroxy propyl methyl cellulose (HPMC) were prepared by ionotropic gelation technique and were evaluated for morphological characters, drug content, loading efficiency, drug–polymer interactions, swelling ratio, mucoadhesive properties, and in vitro release. The resulting microcapsules were discrete, spherical, and free-flowing, and microencapsulation efficiency was 51.28–96.70%.The microcapsules prepared with alginate alone (A4) have exhibited good mucoadhesive property in the in vitro washoff test.The swelling ratio of microcapsules was enhanced with increased alginate concentration. Salbutamol sulfate release from these mucoadhesive microcapsules was slow and extended over a period of 8 h and depends upon the concentration of the alginate. The drug release from alginate- HPMC/carbopol microcapsules followed diffusion-controlled first-order kinetics. The release rate of alginate-HPMC microcapsules (A4H) was higher than other formulations and comparable with commercially available controlled-release capsules. Microcapsules with alginate alone (A4) followed diffusion mechanism. In conclusion, alginate-HPMC/carbopol mucoadhesive microcapsules could be promising vehicle for oral controlled release of salbutamol sulfate.